Dinamika posredovalnih procesov v literaturi - Urbanija, Lučka (Primerjalna književnost, 2009)
In the article I discuss various processes of production and reception on the basis of literary works that, due to their influence, function as an authority and thus open up new intertextual responses. My research focuses on the concepts of "influence" and "intertextuality", as well as on the concept of "literary reception", which integrates both aforementioned concepts. The theme linking the literary works in question and their intertextual relations is that of evil and guilt as it emerges in reading the Book of Job. I will highlight the motif of sin and the figure of Satan. The emphasis will be on the literature of Thomas Mann and Goethe's masterpiece Faust. A detailed analysis of these works also reveals the history of the approaches with which we are confronted during the process of reading.
Keywords: literarna teorija; literary theory; medbesedilnost; literarni vpliv; literarna recepcija; tematologija